102 Three-year evaluation of yield and nutritive value of Tifton-85 bermudagrass and Tifton-85 bermudagrass-alfalfa mixtures produced as baleage in the Southeast. (29th July 2019) - Hendricks, Taylor J; Tucker, Jennifer J; Hancock, Dennis W; Stewart, Lawton; Segers, Jacob R
Abstract: Interseeding a legume, such as alfalfa (Medicago sativa), into bermudagrass (Cynodon dactylon) for baleage production can improve forage quality, reduce supplementation needs, and minimize production losses. The objective of this research was to compare the nutritive value and yield of bermudagrass with and without interseeded alfalfa when produced as baleage. This study was conducted at the University of Georgia Coastal Plain Experiment Station in Tifton, GA, on an established field of 'Tifton 85' (T85) bermudagrass. Ten 0.2-ha plots were randomly assigned to either T85+N or T85 interseeded with 'Bulldog 805' alfalfa (T85+Alf). T85+N received N fertilization (84 kg N/ ha) four times each growing season. Plots were harvested at early bloom stage every 28 to 35 days from 2016 to 2018, baled at 40–60% moisture, and individually wrapped. At each harvest, plots were evaluated for botanical composition and forage yield, and bales were sampled prior to wrapping for nutritive value analysis. Plots were also evaluated for botanical composition using the point-transect method 10 days post-harvest. Data were analyzed using mixed models and least significant differences at α = 0.05. Although seasonal yields were greater in the T85+N during year 1, alfalfa-bermudagrass plots produced at least one additional harvest each season of the study, and on average 8 cuttings per season each year following establishment. Ultimately this contributed to greater (P < 0.0001) cumulative yield in the alfalfa-bermudagrass treatment (34, 783 vs. 25, 608 kg/ha, respectively). Analyses of nutritive value through near-infrared spectroscopy (NIR) show that CP and in-vitro true digestibility (IVTD) were greater (P = 0.005 and P = 0.034, respectively) in the alfalfa-bermudagrass treatment than the bermudagrass-only treatment (14.0 vs 11.4% CP and 66.7 vs. 60.2% IVTD, respectively). Improvements in seasonal yield and nutritive value makes bermudagrass interseeded with alfalfa a viable option for baleage producers in the Southeast.